Childfree: household readiness in the millennial generation from the perspecttive of islamic law - Any Sani’atin,; Rachmad Hidayat, (Technium Social Sciences Journal, 2023)
This research discusses childfreeness in the millennial generation from the perspective of Islamic law. Childfree is an agreement made by a husband and wife not to have children. This research uses a qualitative method. This research is library research where the researcher examines all sources through journals and books that are related to the title being studied. The approach that the author uses in this study is a normative and sociological approach. With the normative approach of the Qur'an and As-Sunnah, having children in Islam is a recommendation, not an obligation. So being child free is not included in the category of prohibited acts, because every married couple has the right to plan and manage their family life, including having children. Even though there are no verses that directly prohibit the freedom of children, choosing not to have children can be considered an unwise choice because Allah SWT guarantees the survival of each of His servants. In Islam, children are seen as gifts to be grateful for because children are gifts from God. Every human being entrusted with being a parent must carry out this role properly and fully.